If 3 (x-1) + 3 (x+1) = 30, then what is the value of 3 (x+2) + 3 x ?

3 (x-1) + 3 (x+1) = 30 => 3^{x}/3 + 3^{x}*3 = 30 => 3 ^{x}+ 3 ^{x}*3*3 = 30*3 => 3 ^{x}+ 3 ^{x}*3^{2} = 90 => 3 (x+2) + 3 x = 90

- If a² + c² + 17 = 2(a - 8b - 2c²), then what is the value of (a³ + b³ + c³)?
- If a +`1/b` = 1 and b +`1/c` =1 , then the value of c +`1/a` is
- What is the highest common factor of (x³ - x² - x - 15) and (x³ - 3x² - 3x + 9)?
- If polynomial P(x) = x
^{3}- 3x^{2}+ 5x-3 is divided by polynomial G (x) = x^{2}- 2, the quotient and remainder are: - ? + (35)² = (130)² - (45)² - 2850
- 125 sweets were distributed equally among children in such a way that the number of sweets received by each child is 20% of the total number of children. How many sweets did each child received
- If a
^{3}+ b^{3}= 6240 and a + b = 30, then find the value of {(a + b)^{2}– 3ab} - If a + b + c + d = 4, then the value of

More Algebra Questions

×